Removal performance, biotransformation pathways and products of sulfamethoxazole in vertical subsurface flow constructed wetlands with different substrates. (February 2023) - Hu, Xiaojin; Huo, Junyu; Xie, Huijun; Hu, Zhen; Liang, Shuang; Zhang, Jian
Abstract: For decades, sulfamethoxazole (SMX) has been frequently detected in the aquatic environments due to its high usage and refractory to degradation. Constructed wetland (CW) is regarded as an efficient advanced wastewater technology to eliminate organic pollutants including SMX. In CW system, substrate adsorption and further biodegradation are extremely important in SMX removal; however, the removal performance of SMX by CWs with different substrates varies greatly, and the biotransformation pathways, products, and mechanisms of SMX remain unclear. To address this, we constructed a CW with conventional substrate (CS, gravel) as control (C-CW) and three CWs with emerging substrates (ES, biochar, zeolite and pyrite for B-CW, Z-CW and P-CW, respectively), and explored the performance and mechanisms of SMX removal in CWs. Results illustrated that the removal performance of SMX in CWs with ES reached 94.89–99.35%, and significantly higher than that with CS of 89.50% ( p < 0.05). Biodegradation contributed >90% SMX removal in all CWs. The microbial compositions and functions differed among CWs at the middle layer (mixed layer), which shaped diverse resistance pattern and metabolism pathways of microbiomes under SMX stress: P-CW and B-CW cope with SMX stress by enhancing material and energy metabolism, whereas Z-CW does that by enhancing metabolism and exocytosis of xenobiotics. Additionally, nine transformation pathways with 15 transformation products were detected in this study. A reversible process of desamino-SMX being reconverted to SMX might exist in P-CW, which caused a lower SMX removal efficiency in P-CW. This study provided a comprehensive insight into the processes and mechanisms of SMX removal in CWs with different substrates, which would be a useful guidance for substrate selection in CWs in terms of enhanced micropollutants removal. Graphical abstract: Image 1 Highlights: Biodegradation contributes more SMX removal in CWs with emerging substrates. Emerging substrates shape higher microbial diversity than conventional substrate. P-CW and B-CW cope with SMX stress by enhancing material and energy metabolism. Z-CW copes with SMX stress by promoting metabolism and exocytosis of xenobiotics.